2009
DOI: 10.1117/12.836064
|View full text |Cite
|
Sign up to set email alerts
|

Modeling laser conditioning of KDP crystals

Abstract: When potassium dihydrogen phosphate crystals (KH 2 PO 4 or KDP) are illuminated by multi-gigawatt nanosecond pulses, damages may appear in the crystal bulk. One can increase damage resistance through a conditioning that consists in carrying out a laser pre-exposure of the crystal. The present paper addresses the modeling of laserinduced conditioning of KDP crystals. The method is based on heating a distribution of defects, the cooperation of which may lead to a dramatic temperature rise. The conditioning is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…And with the increase of laser fluence, smaller and smaller clusters are treated [17]. For the process of multiple-pulses conditioning, it may be understood with defect absorber model.…”
Section: Performance Of Laser Conditioningmentioning
confidence: 99%
“…And with the increase of laser fluence, smaller and smaller clusters are treated [17]. For the process of multiple-pulses conditioning, it may be understood with defect absorber model.…”
Section: Performance Of Laser Conditioningmentioning
confidence: 99%
“…Many studies have shown that body defects introduced in the crystal growth step are the main reason for this induced bulk damage . Therefore, identification of KDP crystal body defects, and development of advanced growth and post processing techniques have been strongly researched in the materials field …”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Therefore, identification of KDP crystal body defects, and development of advanced growth and post processing techniques have been strongly researched in the materials field. [7][8][9][10][11][12] In this paper, for the requirement of high fluence and long life operation of high power solid laser facility, the systematic research were carried out for the initial damage and damage growth behavior of KDP crystal induced by the ultraviolet pulse laser irradiation. We researched the effects of laser pulse energy on damage density and scattering loss KDP crystals, and analyzed micro-morphology characteristics of typical bulk damage.…”
Section: Introductionmentioning
confidence: 99%